The Artifacts which are Being Preserved in the Research Section of Termiz Archeological Museum and its Study - Khudoyberdiyev, Umid (International Journal on Orange Technologies, 2021)
In this article the author describes the information about 27,000 gold, silver and copper coins embossed in our country and abroad, which belong to different periods and are kept in the funds of the Termez Archaeological Museum, and the historical aspect of their study. There isn’t any publication paper in our country and abroad about the coins saved in the Termez Archaeological Museum. Given that the Termez Archaeological Museum was formed in 2002 on the basis of part of the archeological fund of the Surkhandarya Regional Museum of Local Lore, the exhibits in the Numismatic Funds were discovered and handed over to the fund as a result of archeological excavations in the 30s and 40s of the last century. Coins play an important role in the study of human history. Because the information obtained from them is multifaceted. In particular, coins have a place in material resources in solving a number of problems related to history, political economy, language, trade, religious beliefs, the emergence of international relations. If we pay attention to the coins of the IX-XIII centuries, we can see that the coins of this period also have their own number and weight. Given that archaeologists often rely on coins to determine the “age” of cultural layers found during archeological excavations, we can understand how important they are to science.